Incidence of intradialytic hypotension in heart transplant recipients with acute kidney injury treated by acetate-free hemodiafiltration - A. G. Strokov; Ya. L. Poz (Вестник трансплантологии и искусственных органов, 2024)
Introduction. Intradialytic hypotension (IDH) is a common complication of renal replacement therapy (RRT) sessions and may be a particularly detrimental factor in heart recipients. Objective: to investigate the incidence of IDH in heart recipients with acute kidney injury (AKI). Patients and Methods: Two groups of recipients were compared – the study group (SG), n = 313, in which 49 patients required intermittent RRT (IRRT) and in which online hemodiafiltration (OL-HDF) sessions were performed using acetate-free hydrochloric acid-based dialysate fluid; and control group (CG) n = 387, in which 88 patients required IRRT, where standard dialysate with an acetate ion content of 3 mmol/L was used for OL-HDF. Results. There was a significantly lower incidence of IDH in the SG compared to the CG: 10.46% vs 20.47% (p < 0.05). Conclusions. In heart recipients for whom IDH can be considered as a significant adverse factor, the use of acetate-free dialysis fluid can significantly reduce the incidence of this complication.